2012
DOI: 10.2174/2210290601203010099
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents and Pharmacological Activities of Eryngium L. (Apiaceae)

Abstract: Eryngium L. is the largest and arguably the most taxonomically complex genus of the family Apiaceae. The genus has approximately 250 species throughout the world, with the center of diversity in South America. Some Eryngium species are cultivated as ornamental, vegetable, or medicinal crops for folk uses. With increasing chemical and biological investigations, Eryngium has shown its potential as pharmaceutical crops. This review focuses on phytochemistry and pharmacological activities of 127 compounds isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 90 publications
5
86
0
1
Order By: Relevance
“…The phytochemical searches on Eryngium species revealed that this genus contained phenolic compounds, monoterpenes, sesquiterpenes, triterpenoids as well as saponins, flavonoids, coumarin, steroids and acetylenes. Cytotoxic, antimutagenic, anti-inflammatory, antioxidant, antihyperglycemic, anti-snake and scorpion venoms, antibacterial and antifungal activities were previously reported for this genus [6]. In a review of the plants of the American continent with antimalarial activity, E. foetidum water extract, E. nudicaule ethanol extract and E. yuccaefolium water extract were reported to possess antiplasmodial activities.…”
Section: Eryngiummentioning
confidence: 98%
“…The phytochemical searches on Eryngium species revealed that this genus contained phenolic compounds, monoterpenes, sesquiterpenes, triterpenoids as well as saponins, flavonoids, coumarin, steroids and acetylenes. Cytotoxic, antimutagenic, anti-inflammatory, antioxidant, antihyperglycemic, anti-snake and scorpion venoms, antibacterial and antifungal activities were previously reported for this genus [6]. In a review of the plants of the American continent with antimalarial activity, E. foetidum water extract, E. nudicaule ethanol extract and E. yuccaefolium water extract were reported to possess antiplasmodial activities.…”
Section: Eryngiummentioning
confidence: 98%
“…The medicinal parts are dried roots, leaves and flowers (PDR 2000). In folk medicine infusions, extracts, decoctions, liquids and tinctures from the roots are used as a diuretic, antitussive, stimulant, appetizer and aphrodisiac (PDR, 2000;Thiem and Wiatrowska, 2007;Wang et al, 2012). Leaf and root extracts present strong antifungal and moderate antibacterial activity (Thiem et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Saponins identified in E. campestre are interesting because of the acylation by a β,β-dimethylacrylic acid or angeloyl at the C-22 position, which is rare among triterpenoid saponins (Kartal et al, 2005;Kartal et al, 2006;Wang et al, 2012). A phytochemical analysis of the above-ground parts resulted in isolation and structural determination of flavonoids: quercetin, isoquercitrin, rutin, luteolin 7-O-β-D-glucopyranoside, astragalin, kaempferol 7-O-α-L-rhamnopyranoside, kaempferol 3,7-di-O-α-L-rhamnopyranoside, kaempferol-3-O-β-D-(2'-p-E-hydroxycinnamoyl)-glucopyranoside, kaempferol-3-O-β-D-(2'-p-Z-hydroxycinnamoyl)-glucopyranoside (Kartnig and Wolf, 1993;Hohmann et al, 1997;Wang et al, 2012). Simple coumarins: aegelinol benzoate, agasyllin, aegelinol and grandivittin occurred in the roots (Erdelmeier and Sticher, 1985;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eryngium extracts or isolates have shown in vitro bioactivities such as cytotoxicity aganist various human tumor cell lines, anti-inflammatory, anti-snake, and scorpion venoms, antibacterial, antifungal, antimalarial, antioxidant and antihyperglycemic effects. These pharmacological effects of the plant is mainly related to the essential oil compounds such as terpenoids, triterpenoid saponins, flavonoids, coumarins, polyacetylenes and steroids (Celik et al, 2011;Wang et al, 2012). The aerial and root parts of Eryngium maritimum L. and Eryngium kotschyi Boiss.…”
Section: Introductionmentioning
confidence: 99%